1993
DOI: 10.1063/1.465494
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of Hg–Ar van der Waals molecule photofragments following photodissociation

Abstract: We have measured the alignment of the photofragments produced by photodissociation of Hg-Ar van der Waals molecules using light around 253.7 nm. The molecules are produced in the X0+ ground state in a supersonic expansion. Tunable laser light close to the Hg 6 'Se-6 3P, transition is then used to excite the molecule to the Bl* state, in which it dissociates. The alignment of the resulting Hg( 3P,) asymptotic atoms is probed by tuning a delayed second laser to the 435.8 nm Hg 6 3P,-7 3S1 atomic transition and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The present D e from the TT model falls in the experimental range from 133.7 to 142.0 cm −1 . The determination of Quayle et al 45 is especially interesting. They started out with the potential of Ref.…”
Section: Results and Comparison With Previous Determinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present D e from the TT model falls in the experimental range from 133.7 to 142.0 cm −1 . The determination of Quayle et al 45 is especially interesting. They started out with the potential of Ref.…”
Section: Results and Comparison With Previous Determinationsmentioning
confidence: 99%
“…As seen in Table IV, the experimental e = 18.3͑3͒ cm −1 and e e = 0.33͑5͒ cm −1 are actually in very good agreement with the present predictions. It is not clear whether a better analysis with a more realistic potential, similar to what Quayle et al 45 did in the case of Hg-Ar, will resolve the differences in D e and R e .…”
Section: Results and Comparison With Previous Determinationsmentioning
confidence: 99%
“…The purpose of this experiment is to obtain information on molecular state selectivity between the à and B̃ states in the fine-structure process (1) with N 2 and CO. The state selectivity in collisions of excited atoms with rare gases or closed-shell molecules are described as orbital alignment effects of the excited atoms in lots of problems in low-energy atomic collisions. There are two kinds of experimental methods to elucidate the effects of initial orbital alignment of the excited atoms, i.e., (i) precollision alignment method 11-28 and (ii) half-collision alignment method. The half-collision method has already been applied to the present fine-structure process with N 2 and CO, ,, and in the present study, we have employed the precollision alignment method to reveal the alignment effect of the atomic orbital of Hg(6 3 P 1 ). We summarize, here, these methods and their a...…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of situations in the half-collision experiments. In one situation, bound states of stabilized van der Waals (vdW) molecules in supersonic free jets are used as initial states for the photoexcitations, and in another one, free states of transient collision complex are used under thermal energy conditions in gas cell experiments. Spectroscopic studies on intramultiplet predissociations of the Hg(6 3 P 1 )−N 2 and Hg(6 3 P 1 )−CO vdW molecules to Hg(6 3 P 0 ) + N 2 and CO have already been reported. , These studies have shown that the predissociation rate of Hg−N 2 in the à state depends on rotational and vibrational quantum numbers and conclude that the overall rotation of the complex and the bending motion (i.e., restricted internal rotation) of N 2 accelerate the predissociation rate. In addition, the average predissociation rates were almost in the same order for both the à and B̃ states.…”
Section: Introductionmentioning
confidence: 99%